AN ANALYSIS ON FIGURATIVE LANGUAGE OF SONG LYRICS OF ADELE’S ALBUM ENTITLED “25” - Inmunika Hanisfi; Sutami Dwi Lestari; Wageyono (Prodi Pendidikan Bahasa Inggris, Universitas PGRI Banyuwangi, 2022)
Figurative language is a language that uses expressions with different meanings from literal interpretations. This research used thirteen types of figurative language. They are hyperbole, simile, metaphor, personification, irony, metonymy, synecdoche, litotes, symbol, paradox, allegory, antithesis, and sarcasm. This research focuses on analyzing the types of figurative language found on the album entitled “25” by Adele. The objectives of this research are to find out the types and meaning of figurative language of the song lyrics on the album entitled “25” and to find out the most dominant figurative language used in the song lyrics in the album entitled